2018
DOI: 10.1002/ajmg.a.40634
|View full text |Cite
|
Sign up to set email alerts
|

Novel VPS33B mutation in a patient with autosomal recessive keratoderma‐ichthyosis‐deafness syndrome

Abstract: Autosomal recessive keratoderma‐ichthyosis‐deafness (ARKID) syndrome is a rare multisystem disorder caused by biallelic mutations in VPS33B; only three patients have been reported to date. ARKID syndrome is allelic to arthrogryposis‐renal dysfunction‐cholestasis (ARC) syndrome (MIM #208085), a severe disorder with early lethality whose phenotypic characteristics also include ichthyosis, hearing loss, severe failure to thrive, platelet dysfunction and osteopenia. We report on an 11‐year‐old male patient with AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The prevalence of ARC syndrome has not been accurately described, but estimates from gnomAD using the Hardy‐Weinberg principle indicate a carrier frequency of loss‐of‐function variants in VPS33B and VIPAS39 of approximately 9.12e‐6. The broad spectrum of clinical presentations provides additional challenges, as demonstrated by the recent association of autosomal recessive keratoderma‐ichthyosis‐deafness syndrome with biallelic variants in VPS33B in patients in which ARC syndrome was not clinically suspected 29,30 . Further systematic examination of VPS33B and VPS16B expression levels and interactions in primary cells from patients with variants associated with a range of clinical presentations would increase understanding of the roles of these proteins in α‐granule biogenesis and other cellular functions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The prevalence of ARC syndrome has not been accurately described, but estimates from gnomAD using the Hardy‐Weinberg principle indicate a carrier frequency of loss‐of‐function variants in VPS33B and VIPAS39 of approximately 9.12e‐6. The broad spectrum of clinical presentations provides additional challenges, as demonstrated by the recent association of autosomal recessive keratoderma‐ichthyosis‐deafness syndrome with biallelic variants in VPS33B in patients in which ARC syndrome was not clinically suspected 29,30 . Further systematic examination of VPS33B and VPS16B expression levels and interactions in primary cells from patients with variants associated with a range of clinical presentations would increase understanding of the roles of these proteins in α‐granule biogenesis and other cellular functions.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, autosomal recessive keratoderma-ichthyosis-deafness syndrome has recently been associated with rare biallelic variants in VPS33B and may represent a mild phenotypic variant of ARC syndrome rather than a distinct disorder. 29,30 It is not surprising that in diseases involving genes that encode components of multimeric protein complexes, loss of one protein can destabilize the entire complex, as seen, for example, in Hermansky-Pudlak syndrome. 22,23 In vitro studies have indicated that VPS33B and VPS16B (VIPAS39) form a protein complex, 14,15 and knockout of VPS33B in a human megakaryocytic cell line causes severe depletion of VPS16B.…”
Section: Essentialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main symptoms are arthrogryposis multiplex congenita (congenital joint contraction), renal tubular dysfunction and cholestasis (inability of bile to flow from the liver to the duodenum). Additional features include platelet anomalies, central nervous system malformation and ichthyosis (a skin disorder) (Abu-Sa' Da et al, 2005;Alter et al, 2018;Hershkovitz et al, 2008). The symptoms of ARC patients can be largely explained by the major roles of CHEVI in protein recycling and LRO biogenesis (Cullinane et al, 2010;Rogerson and Gissen, 2016).…”
Section: Arc Syndromementioning
confidence: 99%